PENGARUH DIMENSI DARI SUPPLY CHAIN MANAGEMENT TERHADAP KINERJA OPERASIONAL TOKO KOMPUTER DI KOTA AMBON - Zainuddin Latuconsina; Nathalia Dessy Sariwating (Jurnal Cita Ekonomika, 2020)
The purpose of this study was to analyze the effect of information sharing, long-term relationships, collaboration, process integration, and relationship quality on operational performance in Ambon restaurants. The population in this study is a restaurant in the city of Ambon. The sampling technique used was purposive sampling, with a total of 25 respondents. Data were collected using a questionnaire as the main instrument, and the questionnaire used a Likert scale to measure respondents' answers. Partial Least Square is used to identify the effect of supply chain management dimensions on operational performance. The results showed that information sharing affected operational performance (3,167> 2,045), long-term relationships affected operational performance (2,181> 2,045), collaboration affected operational performance (6,720> 2,045), process integration on supply operational performance was not accepted (3,167 > 2,045), while the quality of the relationship does not affect operational performance (0.654 <2.045).